2017
DOI: 10.7196/sajog.1177
|View full text |Cite
|
Sign up to set email alerts
|

Bucket-handle tear of posterior uterine cervical lip in second-trimester unscarred uterus after use of misoprostol: A first report of two cases

Abstract: A bucket-handle tear is a laceration of either the anterior lip or the posterior lip of the cervix so that it hangs like the handle of a bucket. These cervical injuries are more common in term deliveries and are associated with various risks factors, including cervical cerclage, induction of labour, young maternal age, assisted vaginal delivery, prostaglandin use and precipitate labour. We came across two patients who experienced a bucket handle tear of the posterior lip of the cervix in second-trimester abort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…reported a spontaneous delivery through a cervical tear provoked by prostaglandin-induced uterine contractions in a G2P0 woman with a history of cervical dilatation and uterine curettage [ 6 ]. Singhal et al reported the first two cases of bucket-handle cervical tears in a second trimester unscarred uterus after misoprostol use [ 7 ], and Abubeker et al . reported a third similar case in 2020 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported a spontaneous delivery through a cervical tear provoked by prostaglandin-induced uterine contractions in a G2P0 woman with a history of cervical dilatation and uterine curettage [ 6 ]. Singhal et al reported the first two cases of bucket-handle cervical tears in a second trimester unscarred uterus after misoprostol use [ 7 ], and Abubeker et al . reported a third similar case in 2020 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%